An Annotated Checklist of Bird Diversity of Kevdi Eco-campsite, Chhota Udepur, Gujarat - Patel, Shruti; Desai, Pratik; Mesaria, Shalu; Dharaiya, Nishith (Bulletin of Basrah Natural History Museum, 2023)
Birds are considered an indicator of the changing environment. Slight change in the climate and the habitat can disturb the ecosystem and the food web. The present study done in the kevdi Eco-campsite, has 64 species of birds belonging to the 41 families Kevdi-eco campsite is the tourist destination in the Kevdi, Chhota-Udepur district. The checklist delineates the birds present in the area along with their feeding guild. The importance of studying the feeding guilds will guide us in the use of the habitat and niche of the species.